THE INFLUENCE OF K-POP ON SAUDI ARABIAN GOVERNMENT POLICY: A CASE STUDY OF THE K-POP MUSIC FESTIVAL, KCON, IN THE CITY OF RIYADH - Ananda Merlyna Anggraini; Gonda Yumitro; Gautam Kumar Jha; Shannaz Mutiara Deniar (Arabic Literature Department, 2025)
This study examines the influence of K-Pop on Saudi Arabia’s domestic policies concerning national identity, which is strongly shaped by religious values, with the KCON music festival in Riyadh as a case study. Using a literature review of official cultural policy documents, media reports, online sources, and scholarly articles from journals such as the Journal of Ecohumanism, ICMES Journal, and CMES Journal, the study explores how foreign cultural acceptance, particularly Korean culture, has affected policy transformations in Saudi Arabia. Findings indicate two major impacts. First, the reform of the entertainment and cultural sectors, reflected in the government’s authorization of concerts and festivals, investment in cultural infrastructure, and revisions to gender-related regulations in public entertainment. Second, the strengthening of diplomatic and economic ties with Korea, demonstrated through agreements on trade, investment, and technological cooperation. The study acknowledges its limitation in relying solely on secondary sources and recommends future research supported by primary data for a more comprehensive understanding.